Design and Validation of e-monPrakerin Based on Android Technology for Monitoring the Practice of Vocational High School Students - Sutikno Sutikno; Fitri Wardani (Teknodika, 2022)
This study aims to design, construct and validate an e-monPrakerin based Android Technology for Monitoring Vocational High School Students' in Practices. This research belongs to the type of research and development. The draft in the form of an e-monPrakerin model that has been prepared is then given to model, media, language, vocational, and practitioner experts. The process of validating the contents of the e-monPrakerin draft is assessed by an expert forum using an expert judgment technique. Validators consist of lecturers, school supervisors, principals, teachers and practitioners according to their fields so that they can provide criticism and suggestions based on experience. The results of the research have been successful in designing, developing, and validating e-monPrakerin Based on Android Technology. The validation results show that the e-monPrakerin model is considered to have conformity in the aspects of (1) usability, (2) ease of use, (3) ease of learning, (4) updating, (5) stimulating performance, (7) containing contextual insight, (8) general appearance, (9) presentation, and (10) presentation support.